Research Data Management (RDM) in Accordance with the FAIR and CARE principles - Havemann, Jo; Obanda, Johanssen (My University, 2021)
Research projects are usually composed of three or more smaller but highly complex project units that run in parallel generating multiple sets of data. Making these data available upon publication according to the four foundational principles – Findability, Accessibility, Interoperability, and Reusability (FAIR principles) is a standard requirement and established part of there research workflow. This course gives an introduction to Research Data Management (RDM), the contextualisation of datasets by adding relevant metadata, theory and practical application of FAIR and CARE (people & purpose) principles as well as an overview of appropriate research data repositories along with legal and ethical aspects to take into consideration in the process. This presentation was held for the EU project consortium 'Disc4All'
Keywords: Research Data Management; CARE principles; FAIR principles